Intracranial angioleiomyoma: a case series of seven patients and review of the literature - Ivren, Meltem; Cherkezov, Asan; Reuss, David; Haux-Nettesheim, Daniel; Herold-Mende, Christel; Mohr, Alexander; Krieg, Sandro; Unterberg, Andreas; Younsi, Alexander (Journal of neuro-oncology, 2024)
Angioleiomyoma, predominantly arising from the extremities, is a benign soft tissue tumor. Reports on its intracranial location are rare. We assessed clinical, radiological, and pathological features of intracranial angioleiomyoma (iALM) treated at our neurosurgical institution.
Veröffentlicht: 06. Juni 2024
Gesehen am 20.03.2025